Discontinued reasons of journals in SCOPUS: analysis and reflections - Wilches-Visbal, Jorge Homero; Pérez-Anaya, Oskarly; Castillo-Pedraza, Midian Clara (Bibliotecas. Anales de investigación, 2024)
Aim of this article was to examine the reasons for journal discontinuation in Scopus and offers reflections on the subject. It highlights that over 60% of journals are excluded due to poor editorial practices, such as predatory behavior. Additionally, it is observed that most publishers are from Asia, Europe, and the United States. The study emphasizes that non-university journals account for a significant proportion of discontinued journals, being 11 times more likely to be discontinued compared to university journals. It is also noted that only 19.5% of university publishers are Ibero-American. In general, it is concluded that authors need to carefully evaluate the journals in which they intend to publish their research, and it is suggested that they opt for journals supported by university or government institutions for greater reliability and credibility. This study provides valuable insights for researchers and scholars seeking to publish in high-quality scientific journals and avoid those that do not meet adequate editorial standards.